2012
DOI: 10.1098/rspb.2012.0084
|View full text |Cite
|
Sign up to set email alerts
|

Sea lice as a density-dependent constraint to salmonid farming

Abstract: Fisheries catches worldwide have shown no increase over the last two decades, while aquaculture has been booming. To cover the demand for fish in the growing human population, continued high growth rates in aquaculture are needed. A potential constraint to such growth is infectious diseases, as disease transmission rates are expected to increase with increasing densities of farmed fish. Using an extensive dataset from all farms growing salmonids along the Norwegian coast, we document that densities of farmed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
177
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(193 citation statements)
references
References 50 publications
13
177
3
Order By: Relevance
“…Additionally, there seems to be a spatial component in lice abundance on wild fish, suggesting lower lice numbers in the north (Altafjord) (Serra-Llinares et al 2014). A similar spatial pattern in lice abundance was observed in farmed fish (Jansen et al 2012). The high reported 'squared Pearson correlation coefficient' (r 2 = 0.409) between lice numbers in samples of wild salmonids and daily copepodite production in salmon farms (Serra-Llinares et al 2014) could, therefore, be caused by a spatio-temporal covariance in lice abundance on farmed and wild fish.…”
Section: Relationship Between Lice Of Farm Origin and Infection On Wisupporting
confidence: 52%
See 1 more Smart Citation
“…Additionally, there seems to be a spatial component in lice abundance on wild fish, suggesting lower lice numbers in the north (Altafjord) (Serra-Llinares et al 2014). A similar spatial pattern in lice abundance was observed in farmed fish (Jansen et al 2012). The high reported 'squared Pearson correlation coefficient' (r 2 = 0.409) between lice numbers in samples of wild salmonids and daily copepodite production in salmon farms (Serra-Llinares et al 2014) could, therefore, be caused by a spatio-temporal covariance in lice abundance on farmed and wild fish.…”
Section: Relationship Between Lice Of Farm Origin and Infection On Wisupporting
confidence: 52%
“…The high reported 'squared Pearson correlation coefficient' (r 2 = 0.409) between lice numbers in samples of wild salmonids and daily copepodite production in salmon farms (Serra-Llinares et al 2014) could, therefore, be caused by a spatio-temporal covariance in lice abundance on farmed and wild fish. The pairwise timing and location of the correlated data sets thus reflect the spatio-temporal population dynamics of salmon lice, which are closely related with temperature (Schram et al 1998, Stien et al 2005, Jansen et al 2012. It is therefore necessary to account for the effect of temperature to establish whether there is an additional effect of copepodite production in nearby salmon farms when analyzing factors that affect lice numbers in wild salmonids.…”
Section: Relationship Between Lice Of Farm Origin and Infection On Wimentioning
confidence: 99%
“…Statistical models of sea louse population dynamics in Norway [35], stochastic network models of sea louse infection in Loch Fyne, Scotland [36], and hydrodynamic simulations of sea louse production and concentrations in the Broughton Archipelago, British Columbia [28], show how sea louse dynamics can respond to changes in host density among multiple salmon farms and wild salmon populations. Consequently, the relevant spatial scale for critical host-density thresholds in sea louse dynamics, might encompasses several salmon farms, thereby constraining regional production [34].…”
Section: Outbreak and Transmission Dynamicsmentioning
confidence: 99%
“…The Hardangerfjord is one of the fjords with the highest density of salmon farms in the world (Skaala et al 2014). In 2010 the total production of salmon was over 900,000 t. Jansen et al (2012) demonstrated that there was correlation between sea lice on individual salmon farms and local biomass density in the surrounding farms. Severe infections of salmon lice on wild salmonids in the Hardangerfjord coincide with high infection rates at salmon farms (Bjørn et al 2011).…”
Section: Salmonmentioning
confidence: 99%